Políticas de recursos humanos do Banco do Brasil: o discurso e a prática, caminhos de compatibilização - Costa, José Américo Silvares (2002)
This study has as objective to present a proposal to analyze the politics of the Human Resource of the Bank of Brazil utilizing the Theory of sign' (semiotic) as a theory tool, connecting to the organizational usages that had been historically stable and a new speech from the directory body that search for excellence and modernity. It¿s necessary to identify the adequate strategies to manage human resources in a businesses considered excellent and that the Bank search to utilize (benchmarking), doing a semiotic cut, in other words, isolating the communicative aspect, to find how she produces the understanding of what really need to be done at the company. If the purpose of the Bank of Brazil is to reunite an associated team, guided to results progressively better, that makes it even more competitive, and achieve its mission 'to be the solution to services and the finance intermediation, to attend the expectation of clients and shareholders, to fortify the liability between the public functionary and the company and to be useful to society', should implement a model weaved in the daily one of organization to start from the creation of adequate institutional channels rewards (promotions, direct or indirect salaries, training) that privilege the aptitude an constant learning. Through the bibliographical research, will be looked to select illustrious representative texts of the specialized literature that corroborates the idea that the Bank of Brazil possess the necessary management tools to a good management of Human Resources, lacking adjust them, through the acquisition of abilities. For in such a way one will search in internal documents, data on the management of the company, interpreting them to the light of the bibliographical research. Finally it will be included participant comment as link between the theory and the practical one, the speech and the action.'